Moxifloxacin’s Therapeutic Effects in AA-Induced Colitis: Anti-Inflammatory Action through NF-κB Pathway Inhibition, Including TNF-α Pathway and Downstream Inflammatory Processes - Dawood, Jaffar O.; Abu-Raghif, Ahmed (Journal of Contemporary Medical Sciences, 2023)
Objectives: The aim of the present study was to evaluate possible therapeutic effects of moxifloxacin against acetic acid-induced colitis in a rat model. Methods: Forty adult Wistar rats were separated into 4 groups, including the negative control group, acetic acid (AA) group, AA + sulfasalazine (100 mg/kg/day) group, and AA+ moxifloxacin (MFX) (8 mg/kg/day) group. Experimental colitis was induced in rats by rectal administration of (4%v/v) acetic acid. Rats with colitis were received either MFX 8mg/kg/day or sulfasalazine 100mg/kg orally for 7days.The parameters measured are macroscopical assessment, colon weight (indicator of edema) and the measurement of concentrations of the proinflammatory cytokine TNF-α, oxidative stress marker malondialdehyde (MDA), adhesion molecule selectin and the inflammatory mediator NF-κB in colonic tissue homogenate. Results: This study had shown that AA elevate macroscopical scores, colon weight and biochemical homogenate parameters and all measured parameters were significantly reduced by both moxifloxacin and sulfasalazine with nonsignificant difference between them. Conclusions: The study explain that moxifloxacin possesses therapeutic potential in in AA induced colitis and its anti-inflammatory actions may involve inhibition of NF-κB inflammatory pathways including TNF-α pathway with its downstream inflammatory process such as elevation of adhesion molecule synthesis and oxidative species overproduction in the colonic tissues.